A Psychometric Examination of the Coronavirus Anxiety Scale and the Fear of Coronavirus Disease 2019 Scale in the Italian Population - Orrù, Graziella; Bertelloni, Davide; Diolaiuti, Francesca; Conversano, Ciro; Ciacchini, Rebecca; Gemignani, Angelo (Frontiers in Psychology, 2021)
The 2019 Coronavirus Disease (COVID-19) outbreak has caused not only significant physical health problems but also mental health disorders. Anxiety and fear appear to be the main psychological symptoms associated with COVID-19. The aim of this study was to investigate whether anxiety and fear related to COVID-19 are influenced by socio-demographics and if specific conditions, such as positivity for COVID-19 or death among relatives and friends can further enhance these symptoms. In this cross-sectional study, 704 Italians responded to an online survey assessing socio-demographics information, presence/absence of positive cases or deaths due to COVID-19 among relatives or acquaintances. We administered the Coronavirus Anxiety Scale (CAS) and Fear of COVID-19 Scale (FCS-19S) to assess the levels of anxiety and fear associated to COVID-19. Data were collected in November 2020. Anxiety and fear scores positively correlated to each other. Subjects with higher CAS scores also displayed higher FCS-19S scores, in both males and females. CAS and FCS-19S scores tended to increase with age, in fact older individuals exhibited higher scores compared to younger subjects. Additionally, respondents with lower levels of education showed higher scores on both CAS and FCS-19S scale. Similarly, respondents living with older people and/or experiencing the occurred death of one or more relatives, due to COVID-19, exhibited the same outcomes. This study demonstrates how the levels of anxiety and fear, measured by CAS and FCS-19S, associated with COVID-19 are influenced by gender, age, cohabitation status, educational level and the presence of positive cases or deaths due to COVID-19.